Challenging Native-Speakerism in Academic Discourse: A Cor-pusBased Critical Discourse Analysis of Language Education Research - Yulian Purnama; I Nyoman Sudiana (Technology and Society Perspectives (TACIT), 2026)
This study examines the representation of NS/NNS terminology in language education research using a corpus-based critical discourse analysis. The corpus consisted of 94 English-language journal articles published between 1994 and 2026. Quantitative corpus techniques, including frequency, collocation, concordance, and semantic prosody analyses, were integrated with Fairclough's three-dimensional critical discourse analysis framework. The findings reveal four major patterns. First, over 70% of native speaker occurrences are used descriptively without conceptual clarification, indicating their naturalization within academic writing. Second, only 3.1% of the occurrences explicitly challenge the traditional NS/NNS dichotomy. Third, a clear contradiction exists between researchers' critical perspectives on native-speakerism and their continued use of conventional terminology in empirical reporting. Finally, only around 10% of the analyzed articles adopt alternative conceptual frameworks, demonstrating that conceptual transformation remains limited. These findings indicate that academic discourse functions not only as a site of critical reflection but also as a mechanism for reproducing native-speakerist ideology. The study highlights the need for greater critical language awareness, more inclusive terminology, and institutional support to advance the decolonization of English language education.